The Combined Effects of Garlic Extracts (Allium sativum) and Olive Oil (Olea europaea) on Cholesterol Levels - Anindita Hasna Intan Pramono; Endang Ediningsih; Siti Ma'rufah (Nexus Biomedika, 2017)
Introduction:Hyperlipidemia is a risk factor for cardiovascular diseases that cause 56% of ischemic heart disease. The increasing prevalence of degenerative diseases raise the trend of people to seek treatment that is less expensive and easier to obtain, such as garlic extracts (Allium sativum) and olive oil (Olea euopaea). This study aimed to determine the effect of the combination of garlic extracts and olive oil to decrease blood cholesterol levels. Methods: This study was experimental with pretest and posttest controlled group design, performed at the Laboratory of Pharmacology University of Setia Budi Surakarta. The subjects were 30 male rats (Rattus norvegicus), aged 3 months, weighing less than 200 grams, were divided into 5 groups randomly. All groups received high cholesterol diet 14 days before pretest and 28 days during the treatment period. Group I as a negative control untreated. Group II as a positive control group received simvastatin 0,18 mg, Group III, IV and V received a dose of garlic extract successively 0.08 g, 0.16 g and 0.24 g and 0.45 ml dose of olive oil. The data was analyzed using Kruskal Wallis test, Mann-Whitney and Wilcoxon. Results: The result showed the decreasing of total cholesterol (p = 0.015) and LDL (p = 0.014) were significant before and after treatment in each treatment group. In the positive control group did show a significant reduction in total cholesterol compared with the treatment group I (p = 0.347), II (p = 0.251), and III (p = 0.347). While the levels of LDL decline in the positive control group and the treatment also did not differ significantly, with the value of the treatment group I (p = 0.347), II (p = 0.465), and III (p = 0.347). Conclusion:Garlic extracts (Allium sativum) and olive oil can lower blood cholesterol levels of white rats (Rattus norvegicus)similar withsimvastatin effect. Keywords: blood cholesterol, garlic extracts, olive oil